Experience with the WHO Surgical Safety Checklist - Ammar Ali Shah, Tassaduq Khurshid, Abid Latif, Zubair Tariq, Ammar Ali Shah, Tassaduq Khurshid, Abid Latif, Zubair Tariq (Journal of Rawalpindi Medical College, 2017)
Despite years of efforts by organizations throughout the world “wrong site” surgery has proven to be a resilient opponent. The purpose of present review article is to revisit the various tools that have been designed specially the WHO Surgical Safety Checklist (SSCL), the purpose of which is to improve patient safety and prevent errors in the site of surgery. Three items were the corner stone of this review. Firstly effectiveness of the tools specially the WHO SSCL, secondly approach of those responsible for implementation and thirdly adherence by organizations to the provided guideline. A general review of the available data showed a clear improvement in patient safety. As a whole medical personnel considered SSCl and other tools as a good addition but these tools have yet to prove their worth in the prevention of “wrong site” surgery. There is a need to strive continuously for improving patient safety and to capitalize on the advances made in this regard to prevent this menace. At our Rawalpindi Medical University affiliated Holy Family Hospital efforts are in place for improving ways and developing protocols to curb the evil of wrong site surgery. We currently adopted a new way proposed by Ragusa et al in which we experimented with keeping the surgical instruments and trolley outside the OR away from the surgery team members. Thus preventing distraction of team members till the completion of SSCl. Additionally the Anesthetist took the responsibility of the implementation of the SSCL. This method also prevented the hierarchal style seen in the operation theatres. 1,2 These sentinel events policy was published in 1996.3 By the Joint Commission. This commission is an independent body which has 20,500 health care facilities accredited with it in the USA. The aim of this policy was to help individuals and organizations to learn from their mistakes and achieve the objective of patient safety and zero rate of wrong site surgery4. Wrong site surgery mean surgery done on the wrong patient, surgery on the wrong site or may be a wrong surgery on the wrong patient.4 After review of the record the American Academy of Orthopedics claimed that the orthopedic surgeons have a 25% likelihood of operating a wrong site during their careers. After this claim a campaign “Sign Your Site” was started which proposed that surgeons should sign the surgical site before surgery is done.5 A similar scheme known as the “SMaX” which stands for signing, marking and X-ray of the spine segment was launched by the North American Spine Society in 2001.6 In 2004 The Joint Commission proposed a Universal Protocol. The Commission made it compulsory for all medical facilities under its accreditation to adopt it.7 This document included confirmation of patient and surgical site, its marking and time out before any elective surgery. The World Health Organization (WHO) a subsidiary of the United Nations, which is charged with managing the global health affairs, developed the “surgical Safety Checklist” in the year 2008. This checklist was a product of the “Safe Surgery Saves Lives” campaign. According to this document three phases have been identified in any surgery,. i.e., “Sign In” prior to the anesthesia induction, “Time Out” before incision and “Sign Out” before the patient leaves the operating room. 8-10 Unfortunately in 2009 Stahel et al found an increased number of wrong site surgery. 11 This was preceded by the Joint Commission report with similar findings.10 Following these disappointing results the Commission further augmented the importance given to the issue by declaring the Universal Protocol as the National patient Safety Goal.12,13 This review article goes through the studies and literature recently published as SSCL and similar tools that have been developed over time to prevent wrong site surgery and improve patient care. The aim was to identify how effective is the SSCL in achieving its goals. Hurdles in the achieving maximum results were also identified. The thinking and view point of those involved in the implementation were sought, emphasis was also placed on how thoroughly organizations comply with the provided guidelines